The Effectiveness of Protection Mechanisms in Light of the African Charter on Human and Peoples’ Rights - hadjab, yacine (The journal of Teacher Researcher of Legal and political Studies, 2024)
This article discusses the regional protection mechanisms established by the African Charter on Human and Peoples' Rights, specifically focusing on the African Commission on Human and Peoples' Rights as a quasi-judicial body, and the African Court on Human and Peoples' Rights, which complements the role of the Commission. In exploring the effectiveness of these two mechanisms, it is essential to examine their composition, mandates, and procedures.